2018
DOI: 10.1016/j.ifset.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of innovative and conventional food preservation technologies: Process energy performance and greenhouse gas emissions

Abstract: This study aims to establish whether innovative food preservation technologies can offer significant reductions in energy consumption and corresponding greenhouse gas (GHG) emissions while delivering equivalent microbiological lethality, nutritional and organoleptic quality to conventional processes. The energy demand of high pressure processing, microwave, ohmic and conventional heating technologies, for achieving the same pasteurising effect in orange juice under commercially-representative processing condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Current industrial HPP systems operate usually in batch mode, which increases labor costs. Industrial ohmic heaters are of the continuous‐flow type, which are about 20% more efficient for liquid food pasteurization than the batch system studied in this work as the power losses due to voltage switching does not occur (Atuonwu et al, ). Wang et al () also showed empirically that the energy performance of microwave heaters improves with scale.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Current industrial HPP systems operate usually in batch mode, which increases labor costs. Industrial ohmic heaters are of the continuous‐flow type, which are about 20% more efficient for liquid food pasteurization than the batch system studied in this work as the power losses due to voltage switching does not occur (Atuonwu et al, ). Wang et al () also showed empirically that the energy performance of microwave heaters improves with scale.…”
Section: Resultsmentioning
confidence: 99%
“…When the target temperature was reached, the OJ flowed through the holding tube for the desired residence time before subsequent cooling. Further details of each processing equipment are available in Atuonwu et al (). In all the processes, electrical power and energy consumption were measured using Fluke energy meters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations